Tìm đa thức M biết rằng: 1)M+(5x^2-2xy)=6x^2+9xy-y^2 2)M+(2x^2y-2xy^3)=2x^2y-4xy^3 3)(2xy^2+x^2-x^2y)-M=-xy^2-x^2y+1

Question

Tìm đa thức M biết rằng:
1)M+(5x^2-2xy)=6x^2+9xy-y^2
2)M+(2x^2y-2xy^3)=2x^2y-4xy^3
3)(2xy^2+x^2-x^2y)-M=-xy^2-x^2y+1

in progress 0
Iris 2 ngày 2021-12-07T17:25:25+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-12-07T17:27:11+00:00

    `1)M+(5x^2-2xy)=6x^2+9xy-y^2`

    `=> M=(6x^2+9xy-y^2)-(5x^2-2xy)`

    `=> M=6x^2+9xy-y^2-5x^2+2xy`

    `=>M=(6x^2-5x^2)+(9xy+2xy)-y^2`

    `=>M=x^2+11xy-y^2`

    $2)M+(2x^2y-2xy^3)=2x^2y-4xy^3$

    `=>M=(2x^2y-4xy^3)-(2x^2y-2xy^3)`

    `⇒ M= 2x^2y-4xy^3-2x^2y+2xy^3`

    `⇒ M=(2x^2y-2x^2y)+(-4xy^3+2xy^3)`

    `⇒ M=-2xy^3`

    `3)(2xy^2+x^2-x^2y)-M=-xy^2-x^2y+1`

    `⇒ M=(2xy^2+x^2-x^2y)-(-xy^2-x^2y+1)`

    `⇒ M= 2xy^2+x^2-x^2y+xy^2+x^2y-1`

    `⇒ M= (2xy^2+xy^2)+(-x^2y+x^2y)+x^2-1`

    `⇒ M= 3xy^2 + x^2 – 1`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )